Holy bishops in late antiquity: the nature of Christian leadership in an age of transition - Rapp, Claudia (The transformation of the classical heritage, 2005)
Pragmatic authority -- Spiritual authority -- Ascetic authority -- Two unlikely bishops : Synesius of Cyrene and Theodore of Sykeon -- The episcopate : work or honor? -- Social contexts -- Cities -- Empire -- The bishop as a new urban functionary -- Epilogue : holy bishops